The Review of the Two Latest Marketing Techniques; Viral Marketing and Guerrilla Marketing which Influence Online Consumer Behavior (Global Journal of Management and Business Research, 2014)
The internet has developed into a new distribution channel and online trading is increasing rapidly in a decade. This has created a need for us to understand how the consumer perceives online purchases.Online marketing techniques are the art and science of selling products or services over digital networks, such as the Internet and cellular phone networks. Internet in the consumer decision-making process ensures that marketer to make greater use of this tool, while consumers are changing or challenging traditional pattern of supply of the commercial websites.
Keywords: online marketing techniques; consumer perceives; online purchase; digital network